The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41565-022-01086-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced nanobubbles safely ablate vitreous opacities in vivo

Abstract: In myopia, diabetes and aging, fibrous vitreous liquefaction and degeneration is associated with the formation of opacities within the vitreous body that cast shadows on the retina, appearing as 'floaters' to the patient. Vitreous opacities degrade contrast sensitivity function and can cause significant impairment in vision-related quality-of-life. This study introduces 'nanobubble ablation' for safe destruction of vitreous opacities. Following intravitreal injection, hyaluronic acid coated gold nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
(60 reference statements)
2
43
0
1
Order By: Relevance
“…Given the high mRNA delivery efficiency of CADosomes in PBCECs, we next aimed to investigate mRNA delivery in an in vivo rabbit eye model [ [62] , [63] , [64] ]. Many ophthalmic diseases, such as trauma and dry eyes, are due to malfunctions at the level of the cornea, leading to severe visual impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high mRNA delivery efficiency of CADosomes in PBCECs, we next aimed to investigate mRNA delivery in an in vivo rabbit eye model [ [62] , [63] , [64] ]. Many ophthalmic diseases, such as trauma and dry eyes, are due to malfunctions at the level of the cornea, leading to severe visual impairment.…”
Section: Resultsmentioning
confidence: 99%
“…7 D) and a Terminal deoxynucleotidyl transferase dUTP Nick End Labeling (TUNEL) assay (Fig. S8B) indicated that tissue morphology remained intact [ 62 ]. To conclude, this proof-of-concept in vivo data showed the potential of mRNA CADosomes for local nucleic acid delivery towards the cornea.…”
Section: Resultsmentioning
confidence: 99%
“…Bubble implosion comprises bubble topological changes, shock wave emissions, phase transition through supercritical states 1 , and intense pressure and temperature peaks, respectively 2 . Although such effects are traditionally considered to be responsible for damage on material surfaces [3][4][5][6] , cavitation is also exploited in several applications, many of which are in the field of biomedicine, such as drug delivery 7,8 , kidney stones fragmentation 9 , ophthalmic microsurgery 10,11 , eye floaters treatment 12 , and in the field of botany 13,14 . The trend, especially in biomedicine, is to push the technological limit towards the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] As such, GNPs have the potential for extensive medical applications in diagnosis and treatment. In pre-clinical settings, the use of GNPs includes point-of-care diagnostics [9,10] (lateral flow assays such as pregnancy tests and rapid COVID-19 tests), in vivo imaging [11,12] (photoacoustic and computerised tomography), and therapeutics [13][14][15] (photothermal therapy, radiotherapy, catalytic therapy, and drug delivery). Although GNPs treatment designs and applications are rapidly developing with some having reached clinical trials, [16][17][18] none has yet been approved for clinical use primarily because it is hard to predict the changes that nanoparticles undergo and how they behave in complex biological systems.…”
Section: Introductionmentioning
confidence: 99%